A detailed investigation of the multicomponent reaction of salicylaldehyde, ethyl acetoacetate and isocyanides under microwave heating. Issue 39 (30th September 2015) - Amanpour, Tayebeh; Zangger, Klaus; Belaj, Ferdinand; Bazgir, Ayoob; Dallinger, Doris; Kappe, C. Oliver
Abstract: New insights into the cyclocondensation reaction of salicylaldehyde, ethyl acetoacetate and isocyanides are reported. Depending on the reaction conditions either the previously reported 5-hydroxy- N -substituted-2 H -dihydrochromeno[3, 4- c ]pyrrol-2-ones or the novel 2-imino-5-hydroperoxy-5-methyl-2 H -dihydrochromeno[3, 4- c ]furans were obtained. Although suggested as intermediates in previously proposed reaction mechanisms, these hydroperoxides are not obtained when the reaction is performed under open vessel reflux conditions, but are the main product when conducted in a closed vessel using either microwave or conventional heating. Thorough NMR studies and X-ray crystallography confirm the structure of the generated hydroperoxy products. Graphical abstract: